Price Transmission and Trader Entry in Domestic Commodity Markets. - Fafchamps, M; Hill, R (2008)
Using detailed data from three simultaneous surveys of producers, traders, and exporters, this paper examines the transmission of international coffee prices through the domestic value chain in Uganda. We find that producer price fluctuations are inconsistent with constant transaction costs. We investigate three possible explanations for this finding: storage and contango, marketing costs that increase with price, and trader entry that raises search time. We test and reject the storage and marketing costs explanation, but we find some evidence of trader entry in response to a rise in export price. Our findings suggest that small itinerant traders enter in response to an export price increase, probably taking advantage of farmers' ignorance of the rise in wholesale price.